1990
DOI: 10.1007/bf01870075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions of the junctional foot protein and dihydropyridine receptor in skeletal muscle triads

Abstract: Isolated triadic proteins were employed to investigate the molecular architecture of the triad junction in skeletal muscle. Immunoaffinity-purified junctional foot protein (JFP), glyceraldehyde 3-phosphate dehydrogenase (GAPDH), aldolase and partially purified dihydropyridine (DHP) receptor were employed to probe protein-protein interactions using affinity chromatography, protein overlay and crosslinking techniques. The JFP, an integral protein of the sarcoplasmic reticulum (SR) preferentially binds to GAPDH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 48 publications
3
95
2
Order By: Relevance
“…Furthermore, the data indicate that CaMKII␤ M can interact with GAPDH to phosphorylate and modulate its activity in a Ca 2ϩ -and CaM-dependent manner. GAPDH was found to be distributed in muscle cytosol and the SR membrane, and ultrastructural localization studies have also revealed that GAPDH along with other glycolytic enzymes are bound to the cytoplasmic face of the SR membrane in skeletal muscle (33,38). A role for GAPDH together with 3-phosphoglycerate kinase (PGK) has been previously established in the production of ATP from GAP, NAD ϩ , P i , and ADP at the level of the SR membrane (19,20,39,40).…”
Section: Camentioning
confidence: 99%
“…Furthermore, the data indicate that CaMKII␤ M can interact with GAPDH to phosphorylate and modulate its activity in a Ca 2ϩ -and CaM-dependent manner. GAPDH was found to be distributed in muscle cytosol and the SR membrane, and ultrastructural localization studies have also revealed that GAPDH along with other glycolytic enzymes are bound to the cytoplasmic face of the SR membrane in skeletal muscle (33,38). A role for GAPDH together with 3-phosphoglycerate kinase (PGK) has been previously established in the production of ATP from GAP, NAD ϩ , P i , and ADP at the level of the SR membrane (19,20,39,40).…”
Section: Camentioning
confidence: 99%
“…Triadin is a junctional SR protein discovered in 1990 by Brandt et al (1990) that was originally proposed to play a critical role in excitation-contraction (EC) coupling (Kim et al, 1990). However, since the bulk of the protein is located within the SR lumen where it binds to CSQ and the RyR (Knudson et al, 1993b;Guo and Campbell, 1995), it is currently believed to facilitate cross-talk between CSQ and the RyR (Beard et al, 2002), rather than directly infl uence EC coupling (Gyorke et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently som~ of us have presented evidence that triadin is a major constituent of the triad junction which binds both to the DHP receptor and the JFP [11,12]. This protein is an intrinsic protein of the terminal cisternae (TC) with a distribution and content approximately the same as those of the J FP [13].…”
Section: Introductionmentioning
confidence: 99%